Quality changes of Larimichthys crocea pretreated by ultrasonic-assisted immersion under cold storage at 4 °C - Chenchen Zhang; Jinfeng Wang; Jing Xie (Ultrasonics Sonochemistry, 2023)
The effects of several ultrasonic treatments during cold storage at 4 °C on the quality of large yellow croaker (Pseudosciaena crocea) were suggested. Large yellow croaker fillets were divided into six different groups for treatment. (a) CK (without any treatment), (b) A (single frequency 20 kHz), (c) B (single frequency 40 kHz), (d) C (left and right dual frequency 20 + 40 kHz), (e) D (orthogonal dual frequency: left and right 40 kHz, upper and lower 20 kHz), and (f) E (orthogonal dual frequency: left and right 20 kHz, upper and lower 20 kHz). The samples were divided into six groups, placed in sterile PE bags, and chilled to 4 °C. In order to determine the impact of ultrasonic treatment on the quality of large yellow croaker during cold storage, microbial indicators and physical and chemical indicators were measured every 3 days. The total number of colonies, the percentage of psychrophilic bacteria, the sample's pH, and its TVB-N value were all shown to grow at a much slower pace following ultrasonic treatment. In addition, the antibacterial effect of dual frequency ultrasound was gradually better than that of single frequency ultrasound. In conclusion, Group D has a pretty excellent impact on preserving overall sample quality.